Lithium aluminosilicate glass, glass ceramic made

By optimizing the composition and manufacturing process of lithium aluminosilicate glass, the chromaticity, brightness and scattering problems of transparent glass ceramics at high temperatures are solved, and the effects of low chromaticity, high brightness and low scattering are achieved, improving the durability and economic productivity of the material.

CN119551907APending Publication Date: 2025-03-04SCHOTT AG
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411869445.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2020-02-28
Filing Date
2021-03-01
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing transparent glass ceramics have problems of low chromaticity, low brightness and high scattering during the manufacturing process, and it is difficult to meet the durability and appearance requirements of materials at high temperatures.

Method used

Using a specific composition of crystallizable lithium aluminosilicate glass, the nucleation and crystallization process of glass ceramics is controlled by optimizing the content range of components such as Li2O, Al2O3, SiO2, TiO2, ZrO2, SnO2 and MgO to achieve low chrominance, high brightness and low scattering effects.

Benefits of technology

It realizes the low chrominance, high brightness and low scattering of transparent glass ceramics, shortens the ceramicization time, and improves the economic productivity and application performance of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119551907A_ABST
    Figure CN119551907A_ABST
Patent Text Reader

Abstract

The present invention relates to a crystallizable lithium aluminosilicate glass for the manufacture of transparent glass ceramics, comprising the following component (in terms of oxide wt.%) # imgabs0 condition: (both in terms of wt.%): 0.005 < MgO * SnO2 < 0.06 (condition B1a). The invention also relates to a glass ceramic produced from such a glass and to the use thereof.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of patent application 202110225913.3 filed on March 1, 2021, with the invention name of "Lithium aluminosilicate glass, glass ceramics made therefrom, manufacturing methods and uses thereof". Technical Field

[0002] The invention relates to a crystallizable lithium aluminosilicate glass according to the preamble of claim 1 which can be converted into an LAS glass ceramic.

[0003] The invention also relates to a glass ceramic produced from such a glass, a method for producing a glass ceramic and the use of such a LAS glass ceramic. Background Art

[0004] LAS glass ceramics are widely used due to their special material properties, such as their low expansion coefficient and their high resistance to temperature differences and temperature changes, their high strength, their chemical resistance and their transparency. In general, the thermal expansion behavior is set so that the material has a very low expansion coefficient within its application temperature range, usually α 20 / 700 <0±1.5·10 -6 / K. Requirements for use at high temperatures include that the glass-ceramic maintains the required properties (e.g. thermal expansion, transmittance, temperature resistance) during its service life. In terms of temperature resistance, low shrinkage of glass-ceramic (compacted) at high temperatures is a key variable. Because glass-ceramic products are usually heated unevenly during use, stresses accumulate in the product over time due to different local shrinkage levels.

[0005] Common uses for LAS glass ceramics are fire-resistant enamels, cookers, transparent fireplace windows, oven windows and as cooktops. When used as cooktops, the transparent glass ceramic panels are either pigmented with colored oxides or coated with an opaque, usually colored coating on the underside to prevent the user from seeing through the technical built-in components and to provide a colored impression. The cutouts in the underside coating can be equipped with colored and white displays, usually light-emitting diodes or screens.

[0006] Transmission and scattering are important properties for the appearance and optical properties of glass-ceramics.

[0007] One such category of glass ceramics is the transparent colorless glass ceramics, in whose manufacture no coloring compounds are added. Another category is the transparent colored glass ceramics, which are usually volume colored by adding V2O5 to reduce the brightness and obtain a black appearance. This is a typical treatment for cooktops with a black appearance.

[0008] For transparent colorless glass ceramics, high transparency is desired, i.e. high brightness and low chromaticity. Both of these indicate low absorption, since absorption bands reduce brightness and deepen colors, depending on their position in the visible spectrum. Thus, the brightness of such glass ceramics with a thickness of 4 mm is generally above 80%.

[0009] In this document, brightness may also be related to the term "light transmittance" or "overall transmittance".

[0010] However, transparent colorless glass ceramics have low color due to the nucleating agent TiO2 and possible SnO2 and the impurities (especially iron-containing impurities) present in the batch raw materials (Gemengerohstoff). This is not ideal and is minimized as much as possible through technical measures.

[0011] Another essential characteristic of LAS glass ceramics is scattering, which is determined by the crystal size, birefringence and the difference in refractive index between the crystal and the residual glass. Generally speaking, a small amount of scattering is required so that no perspective distortion occurs and the display is clearly visible. In special applications, it is also necessary to control the scattering in order to produce a translucent white appearance, for example.

[0012] Brightness or light transmittance is described by the lightness value Y (brightness) according to the CIE standard color system or the L* value in the CIELAB color system. The German implementation of the international CIE standard is specified in DIN 5033. The CIELAB color model is defined in the standard DIN ENISO11664-4 "Colorimetry - Part 4: CIE 1976 L*a*b* color space".

[0013] Within the scope of the invention, the spectrophotometric method required for this purpose measures the polished sample in the spectral range of 380 nm to 780 nm. From the spectral values ​​measured in the range representing the visible spectrum, the light transmittance is calculated by selecting a standard light source of a given thickness and an observer angle.

[0014] The convention for glass ceramics is to use the variable c* (chroma) as a measure of color in the CIELAB color system with coordinates L*, a*, b* according to the following calculation:

[0015]

[0016] In a known manner, the coordinates of the CIELAB color system can be calculated from the color coordinates of the CIE color system and the lightness Y. The c* value of the sample is determined by spectrophotometrically measuring the transmittance using the parameters of the selected standard illuminant and observer angle.

[0017] Scattering in glass ceramics is determined by measuring haze. According to ASTM D1003-13, haze is the percentage of transmitted light that deviates by more than 2.5° from the incident beam on average.

[0018] The large-scale production of transparent glass ceramics is carried out in several stages. First, a crystallizable initial glass is melted and clarified from cullet and powdered batch raw materials. The temperature of the glass melt reaches 1550°C to a maximum of 1750°C, usually up to 1700°C. In some cases, high-temperature fining above 1750°C is used, usually at temperatures around 1900°C. Arsenic oxide and antimony oxide are technically and economically suitable fining agents for transparent glass ceramics, which have good bubble quality at conventional fining temperatures below 1700°C. Arsenic oxide is particularly beneficial for the transparency of glass ceramics (high brightness and low chroma). Even if these fining agents are firmly incorporated into the glass lattice, they still have disadvantages in terms of safety and environmental protection. For example, special precautions must be taken when extracting the raw materials, preparing the raw materials and during the glass manufacturing process due to the evaporation of the melt. Therefore, considerable development work has been invested in replacing such substances, but this encounters technical and economic disadvantages.

[0019] After melting and fining, the glass is usually hot formed by casting, pressing, calendering or floating. For many applications, glass ceramics are required to be in a flat shape, such as a sheet. Calendering and float processes are used to make flat sheets. In order to produce such LAS glasses economically, low melting temperatures and low processing temperatures V during hot forming are required. A。 Furthermore, the glass must not exhibit any devitrification during forming, in other words, no large crystals larger than about 5 μm should be formed, which would reduce the strength of the glass-ceramic article or cause visual disturbance. A (Viscosity 10 4 dPas), so it is necessary to ensure that the upper limit of the devitrification temperature of the melt is close to, preferably lower than, the processing temperature to avoid the formation of large crystals. During the molding by calendering, it is critical that the molten glass contacts a drawing nozzle made of a precious metal (usually a Pt / Rh alloy), and then the glass is molded and cooled by calendering. During the float process, it is critical that the glass contacts the nozzle and the front of the float tank contacts the liquid Sn, where the glass has a high crystal growth rate.

[0020] In the subsequent temperature process, the crystallizable LAS glass is converted into a glass ceramic by controlled crystallization (ceramicization). This ceramicization is carried out in a two-stage temperature process, in which nuclei are first formed, usually from ZrO2 / TiO2 mixed crystals at a temperature of 680°C to 800°C. SnO2 also participates in the nucleation. At high temperatures, high quartz mixed crystals grow on these nuclei. At a maximum manufacturing temperature of about 900°C, the structure of the glass ceramic is homogenized and the optical, physical and chemical properties are adjusted. Shortening the ceramicization time is conducive to economical production.

[0021] When the temperature is increased in the temperature range of about 950° C. to 1250° C., a further transformation into a keatite mixed crystal occurs. With this transformation, the thermal expansion coefficient of the glass ceramic increases, and the transparent appearance changes to an opaque appearance through further crystal growth and the light scattering associated therewith.

[0022] In this document, as the name of the crystal phase, the synonyms of high quartz mixed crystals are "β-quartz" or "β-eucryptite", and the synonym of hydrothermal quartz mixed crystals is "β-spodumene".

[0023] It is increasingly common to use the environmentally friendly fining agent SnO2 alone or in combination with one or more fining additives (such as halides (F, Cl, Br), CeO2, MnO2, Fe2O3, sulfur compounds) as a substitute for arsenic oxide and antimony oxide.

[0024] However, the use of SnO2 has disadvantages. SnO2 itself is technically less effective as a fining agent and requires higher temperatures to release the fining active oxygen. High concentrations of SnO2 in the case of the used As2O3 in the order of about 1 wt.% are disadvantageous because during hot forming, Sn-containing crystals can devitrify. A second major disadvantage of transparent glass-ceramics when using tin oxide instead of arsenic oxide as a fining agent is that SnO2 causes additional absorption and a darkening of the color. The absorption is mainly based on the color-forming complex with the nucleating agent TiO2. At higher fining temperatures, the absorption increases with the Sn content. 2+ The absorption increases with the increase of the ratio of Sn / Ti, so the absorption is enhanced. The color of the Sn / Ti color-forming complex is darker than the known Fe / Ti color-forming complex, and this defect makes it difficult to replace the clarifier arsenic oxide with tin oxide in transparent glass ceramics. The Fe / Ti color-forming complex produces a reddish brown color, while the Sn / Ti color-forming complex produces a yellowish brown color. The absorption mechanism of these two color-forming complexes is probably based on the electron transition (charge transfer) between two adjacent multivalent cations.

[0025] The formation of the charge transfer color complex is mainly carried out during crystallization. In order to reduce the concentration of the color complex, it is advantageous to shorten the nucleation and crystallization time. On the contrary, shortening the nucleation time will lead to enhanced light scattering, while shortening the crystallization time will lead to uneven products.

[0026] The technical ingredients of the melt contain other coloring elements such as Cr, Mn, Ni, V, and especially Fe as impurities. In addition to the Fe / Ti coloring complex, Fe also ionizes and colors into Fe 2+ or Fe 3+ However, due to the high cost of iron-poor raw materials, it is very uneconomical to reduce the Fe2O3 content to values ​​below about 50 ppm.

[0027] In some mature glass-ceramics applications, special heat-resistant glasses such as aluminosilicate glass or borosilicate glass are increasingly used. Other technical measures such as air cooling of chimney windows or electronic temperature limitation of induction heating cooktops can reduce the operating temperature and also enable the use of these special glasses as appropriate. Compared with these glasses, the color of transparent glass-ceramics is the main disadvantage. Therefore, it is necessary to develop a transparent glass-ceramic with low chromaticity.

[0028] The method of avoiding (WO 2008 / 065167 A1) or limiting (WO 2008 / 065166 A1) the nucleating agent TiO2 as a coloring complex in glass ceramics has not yet reached technical implementation. The need for higher content of alternative nucleating agents ZrO2 and / or SnO2 will lead to disadvantages during melting and forming, such as higher melting temperature and forming temperature and insufficient resistance to devitrification during forming.

[0029] Patent document WO 2013 / 124373 A1 describes the physical decolorization of transparent glass ceramics containing high quartz mixed crystals as the main crystal phase by adding 0.005wt.% to 0.15wt.% Nd2O3, which does not contain arsenic and antimony except for unavoidable raw material impurities. The physical decolorization principle is based on the neutralization of existing absorption bands with complementary absorption bands of the decolorizing agent. This naturally leads to stronger light absorption and thus reduces brightness. In order to obtain favorable manufacturing conditions, namely low melting temperature and low forming temperature, the exemplary glass in this document contains a high content of viscosity-reducing component MgO of 0.44wt.% to 0.93wt.%. In addition to the high MgO content, the higher SnO2 content of the exemplary glass ceramics is also not conducive to the chromaticity c*.

[0030] Patent document WO 2013 / 171288 A1 discloses transparent, light-colored and non-scattering glass-ceramic products, glass-ceramics and precursor glasses with high quartz mixed crystals. Except for unavoidable trace amounts, the composition of LAS glass-ceramics does not contain arsenic oxide, antimony oxide and rare earth oxides such as Nd2O3. The glass contains a higher SnO2 content in order to achieve an ideal clarification effect. The example glass in the invention does not contain any MgO to improve the color, so as to achieve high melting temperatures, especially to increase the processing temperature V AFor calendaring, the higher temperatures mean a narrower process window and less system downtime.

[0031] Patent document WO 2016 / 038319A discloses a transparent, colorless and non-scattering glass ceramic plate, which contains high quartz mixed crystals, and the selected composition of its chemical composition does not contain any oxides of As, Sb and Nd. The minimum content of the clarifier SnO2 should be selected to a high value to ensure sufficient bubble quality. The color composition range disclosed in the document has disadvantages. The color value b* of the present disclosure is almost equal to 6.4.

[0032] Therefore, during the development process, a whole set of relative requirements for glass and glass ceramics need to be coordinated, such as good manufacturing properties without compromising the product quality of the glass ceramics, especially color, brightness, shortened ceramicization time and reduced scattering. Summary of the invention

[0033] The object of the present invention is to provide a crystallizable lithium aluminosilicate glass:

[0034] - It has good manufacturing properties that facilitate economical production;

[0035] -The transparent glass ceramics produced in this way have low chromaticity, high brightness and low scattering, and the ceramicizing time is shortened.

[0036] The solution of the invention for achieving the above-mentioned object is a crystallizable lithium aluminum silicate glass having the features of claim 1 and a glass ceramic produced therefrom having the features of claim 17 .

[0037] Another object of the present invention is to provide a method for producing glass and glass ceramics and their use. The solution of the present invention for achieving the above-mentioned objects is the subject of other independent claims.

[0038] The crystallizable lithium aluminosilicate glass according to the invention and the glass ceramics according to the invention made or producible therefrom have the following composition (in wt. % of oxides):

[0039]

[0040]

[0041] The conditions are (both are calculated in wt.%): 0.005<MgO×SnO2<0.06 (Condition B1a).

[0042] The values ​​in condition B1a have the dimension (wt.%) 2 .

[0043] Li2O, Al2O3 and SiO2

[0044] The oxides Li2O, Al2O3 and SiO2 are essential constituents of a high quartz mixed crystal phase and / or a keatite mixed crystal phase within specified limits.

[0045] For crystallizable glasses and glass ceramics made therefrom, the Li2O content should be 3 wt.% to 5.0 wt.%. A minimum content is required to achieve the desired low glass processing temperature. It has been shown that at contents above 5 wt.%, it is difficult to achieve the desired zero thermal expansion of the glass ceramic. Contents above 5 wt.% are also disadvantageous with regard to the desired low chromaticity c* of the glass ceramic. The Li2O content is preferably less than 4.5 wt.%, more preferably less than 4.2 wt.%, particularly preferably less than 4 wt.%. The minimum content is preferably 3.2 wt.%, particularly preferably 3.4 wt.%.

[0046] The preferred range is 3 wt.% to <4.5 wt.%.

[0047] The Al2O3 content is 19wt.% to 24wt.%. A content higher than 24wt.% is disadvantageous because mullite tends to devitrify during molding. It has also been shown that the higher the content, the more scattering occurs when the ceramicization time is shortened. Therefore, the portion is preferably at most 23wt.%. The minimum content is 19wt.%, because Al2O3 is conducive to the low processing temperature and low chromaticity c* of glass ceramics. The minimum content of Al2O3 is preferably at least 20wt.%.

[0048] The main component SiO2 content should be at least 62wt.%, because this is conducive to the required glass ceramic properties, such as low thermal expansion and chemical resistance. In addition, reduce the scattering under the situation of shortening the ceramicization time. Particularly advantageously, the minimum content is 64wt.%. SiO2 content should be up to 70wt.%, because this component can improve the processing temperature and the melting temperature of glass. SiO2 content is preferably up to 68wt.%.

[0049] Nucleating agents TiO2 and ZrO2

[0050] As an effective nucleating agent, the component TiO2 is essential for the transparency of glass ceramics. It promotes high nucleation speed, so that even with shortened ceramizing times, sufficient nucleation is achieved, thus reducing the average crystallite size. At the same time, even with shortened ceramizing times, glass ceramics are obtained whose scattering does not interfere with vision.

[0051] However, due to the formation of Fe / Ti color complex and Sn / Ti color complex, a higher TiO2 content is essential. Therefore, the TiO2 content should be higher than 1.6wt.% but at most 2.8wt.%. The TiO2 minimum content is preferably 1.8wt.%. This minimum content is conducive to shortening the ceramicization time to prevent scattering. The TiO2 content is particularly preferably higher than 2wt.%.

[0052] In order to limit color effects, up to 2.6 wt. % TiO2 is preferably included.

[0053] ZrO2 is provided as another nucleating agent. The ZrO2 content is 1 wt.% to 2.5 wt.%. The ZrO2 content is preferably limited to less than 2.2 wt.%, more preferably less than 2 wt.%, because higher contents are detrimental to the melting behavior of the ingredients during glassmaking and devitrification may occur during forming due to the formation of zirconium-containing crystals. This component helps to avoid too high a content of the alternative nucleating agent TiO2, which is therefore beneficial for providing a glass-ceramic with a low chromaticity c*. The minimum ZrO2 content is preferably 1.6 wt.%.

[0054] SnO2

[0055] The selection of the SnO2 content is of particular importance within the scope of the present invention, especially since this component is crucial for the color of the glass ceramic since Sn / Ti color species are formed during the crystallization process.

[0056] During conventional forming by water-cooled calendering, special attention has been paid to the manufacturing characteristics. WO 2013 / 124373A1 discloses large-scale industrial tests on SnO2-refined LAS glass containing 0.18 wt.% SnO2, showing that a Sn-containing coating is established on the roller during forming. Based on the role of tin oxide as a nucleating agent, this roller coating comes into contact with the glass melt and gradually induces surface crystallization on the cooling glass ribbon. This is visually very obvious and the strength may decrease. Removing the roller coating involves production losses. With the present invention, the economic disadvantages caused by this roller coating can be reduced.

[0057] In addition, the glass sheet undergoes thermal deformation when passing through the burner, and due to reheating, the particles pressed into the roller coating may induce crystallization of bending marks, which grow during the ceramicization process and cause visual disturbances. Such deformed glass ceramic products are used, for example, as chimney windows bent at a certain angle.

[0058] In order to avoid these disadvantages, the SnO2 content is limited compared to the prior art and is less than 0.15 wt.%, preferably less than 0.12 wt.%, preferably less than 0.10 wt.%, more preferably less than 0.08 wt.%, and particularly preferably less than 0.05 wt.%. As the SnO2 content decreases, the color and roller coating continue to decrease. SnO2 below 0.10 wt.% indicates that the formation of surface crystals during molding is significantly improved.

[0059] The lower limit of SnO2 requires a minimum content of 0.01 wt.%. In particular, when the fining agents arsenic oxide or antimony oxide are not used, the polyvalent tin oxide resists the formation of bubbles on the precious metal built-in parts in the molten bath (reboiling). Even at low contents, SnO2 can still be used as a fining agent and, in combination with the technical measures of the molten bath, can ensure the required bubble quality. Glass and glass ceramics made therefrom preferably contain at least 0.03 wt.%, particularly preferably at least 0.04 wt.% SnO2.

[0060] Taking into account aspects concerning low color and economical manufacturing characteristics, a particularly preferred SnO2 range is 0.03 wt.% to <0.10 wt.%.

[0061] MgO

[0062] Another key component to achieve the desired glass-ceramic properties is the MgO content. The MgO component is an integral part of the mixed crystal and residual glass phase, so it has a great influence on many properties. This component reduces the melting temperature and processing temperature of the glass, thereby promoting economic production. The MgO content is at least 0.01wt.%, preferably at least 0.05wt.%, more preferably at least 0.1wt.%, and particularly preferably at least 0.15wt.%. In glass-ceramics, this component increases thermal expansion and causes particularly unfavorable color enhancement. This is attributed to promoting the formation of Fe / Ti color species and Sn / Ti color species.

[0063] The MgO content should be less than 0.5 wt.%, preferably at most 0.4 wt.%, particularly preferably at most 0.35 wt.%. In the preferred MgO range of 0.1 wt.% to 0.4 wt.%, the requirements for low color and low processing temperature of the glass ceramic can be combined particularly well. The thermal expansion of the glass ceramic can be set to near zero expansion.

[0064] MgO×SnO2

[0065] The composition product MgO×SnO2 is decisive for the coordination of low chromaticity, clarity and low melting and forming temperatures. This allows the chromaticity c* to be further reduced, the brightness Y of the glass ceramic to be further increased, and the disadvantages compared to special glasses with high brightness and low chromaticity to be reduced while being economically produced.

[0066] The composition product MgO×SnO2 of the glass according to the present invention (both in wt.%) is less than 0.06, preferably less than 0.05, preferably less than 0.04, more preferably less than 0.03, and particularly preferably less than 0.025. The composition product should be greater than 0.005, preferably greater than 0.01, more preferably greater than 0.012, and particularly preferably greater than 0.015.

[0067] This is necessary to reconcile the desired good manufacturing properties of the glass with low chroma and high brightness.

[0068] Advantageously, the composition product applies: 0.01<MgO×SnO 2 <0.05 (condition B1b).

[0069] In a series of tests with varying MgO and SnO contents, it was found that the MgO content influences the absorption of the Sn / Ti chromogenic complex in a characteristic manner. Optical evaluation of the spectrum shows that the blue Sn / Ti absorption band is influenced not only by its intensity but also by its position in the visible spectrum. Due to the reduction in the MgO content, the absorption band is shifted to its maximum in the direction of the invisible UV range. The sensitivity of the human eye is lower here, which leads to the expected reduction in chromaticity and increase in brightness. The overall effect is particularly advantageous if the intensity of the Sn / Ti absorption band is reduced due to the low SnO2 content. Therefore, in view of condition B1a and especially in view of condition B1b, the low content of MgO and SnO2 according to the invention is the essential element for the desired transparency, high brightness and low chromaticity c*. Transparency means high brightness Y and low chromaticity c*. Preferred values ​​are Y>83% and c*≤4.

[0070] A very narrow composition range was found that combines favorable manufacturing properties with the low chromaticity, high light transmittance and low scattering of LAS glass ceramics. In particular, the low chromaticity of the transparent glass ceramics according to the invention is closer to the typical values ​​of temperature-stable special glasses, where the chromaticity c* is generally less than 1.

[0071] Advantageous manufacturing characteristics for economical production include low cost batching raw materials, low melting and forming temperatures, resistance to devitrification and short ceramicization time. With the shortened ceramicization time, high brightness can be achieved without causing visually disturbing light scattering (haze).

[0072] In addition, compared with the prior art, there is an advantage in increasing the ratio of nucleating agent TiO2 / SnO2. Preferably, 18≤TiO2 / SnO2<200 (condition B2) is applicable. This ratio is more preferably at least 20, particularly preferably at least 25. Both components will increase the chromaticity, especially due to the absorption of Sn / Ti color-forming complexes. The low SnO2 content according to the present invention will reduce the concentration of these color-forming complexes and achieve the desired high brightness and low chromaticity. The TiO2 content can be selected as a higher value to increase the ratio. In this way, a shortened ceramicization time can be achieved without interfering scattering and improved resistance to devitrification. The preferred upper limit is less than 100.

[0073] The sum of nucleating agents TiO2+ZrO2+SnO2 (condition B3) preferably applies a range of 3.8wt.% to 4.8wt.%. Sufficiently fast nucleation requires a minimum content. The minimum content is preferably 4wt.% in order to further reduce scattering in the case of rapid ceramicization. The upper limit of 4.8wt.% is due to the need for anti-devitrification.

[0074] Alkali Metals

[0075] Alkali metals Na2O and K2O reduce the melting temperature and processing temperature of the glass during molding. They promote the melting of the insoluble raw materials ZrO2 and SiO2. The content of these two must be limited to a maximum of 1.5 wt.%, because these two components should not be incorporated into the crystalline phase, but should remain in the residual glass phase of the glass ceramic. Too high a content will affect the crystallization behavior of the crystallizable initial glass into glass ceramics and have a negative effect on the durability / temperature resistance of the glass ceramics.

[0076] The Na2O content is preferably 0 wt.% or >0 wt.%. The glass particularly preferably contains at least 0.1 wt.% Na2O. Preferably, the maximum proportion is preferably 1.5 wt.%, in particular 1 wt.%. The Na2O proportion is preferably 0.1 wt.% to 1.5 wt.%.

[0077] The K2O content is preferably 0 wt.% or >0 wt.%. The glass particularly preferably contains at least 0.1 wt.% K2O. Preferably, the maximum proportion is preferably 1.5 wt.%, in particular 1 wt.%. The K2O proportion is preferably 0.1 wt.% to 1.5 wt.%.

[0078] In a preferred embodiment, 0.2 wt.% ≤ Na2O + K2O ≤ 1.5 wt.% applies (condition B4a). The sum of alkali metal Na2O + K2O is more preferably not more than 1.2 wt.%. The sum of alkali metal Na2O + K2O is particularly preferably at least 0.4 wt.% to further improve the meltability and reduce the processing temperature. Particularly preferably, 0.2 wt.% ≤ Na2O + K2O ≤ 1.2 wt.% applies (condition B4b).

[0079] It has been shown that the component Na2O is more favorable than K2O in lowering the melting temperature. Therefore, it is preferred that the content of Na2O is higher than the content of K2O (both in wt.%). It is particularly advantageous if 1<Na2O / K2O≤10 (condition B5) applies. The lower limit of the ratio of Na2O / K2O is preferably 2. The upper limit of the ratio of Na2O / K2O is preferably less than 8.

[0080] Alkaline earth metals

[0081] Like the alkali metals Na2O and K2O, the alkaline earth metals CaO, SrO and BaO are not incorporated into the mixed crystal phase, but remain in the residual glass phase of the glass ceramic. They help to reduce the melting temperature and processing temperature. Too high a content will affect the nucleation and crystallization behavior of the crystallizable glass into glass ceramics and have a negative effect on the durability / temperature resistance of the glass ceramics.

[0082] It has been confirmed that the CaO component is beneficial to reduce the processing temperature V A And improve the anti-devitrification. However, it will lead to the increase of color deepening and scattering under the situation of shortening the ceramicization time. The CaO content is up to 2wt.%, preferably up to 1wt.%. It is particularly preferred that the upper limit of the CaO content is lower than 0.8wt.%, so as to minimize the scattering under the situation of shortening the ceramicization time. CaO is preferably equal to 0wt.% or>0wt.%, particularly preferably ≥0.05wt.%, more preferably at least 0.1wt.%, particularly preferably at least 0.3wt.%. The preferred range is 0.05wt.% to 2wt.%.

[0083] The BaO content is preferably at most 4 wt.%. The SrO content is preferably at most 2 wt.%. The BaO content is preferably at most 2.5 wt.%. The SrO content is preferably at most 1.5 wt.%. The BaO content is particularly preferably 0 wt.% or >0 wt.%, at least 0.2 wt.%.

[0084] The preferred range of BaO is 0.2 wt. % to 2.5 wt. %.

[0085] The SrO content is preferably 0 wt.%, particularly preferably >0 wt.%, in particular ≥0.01 wt.%.

[0086] The preferred range of SrO is 0.01 wt. % to 2 wt. %.

[0087] In order to reduce the melting temperature and processing temperature, preferably, the sum of the SrO content and the BaO content is 0.5 wt.% to 2.5 wt.% (Condition B6). A higher content is not conducive to the durability / temperature resistance of the glass ceramic.

[0088] Alkali metal Na2O, K2O and alkaline earth metals CaO, SrO, BaO not only accumulate in the residual glass phase between the crystals, but also accumulate on the surface of glass ceramics. In the ceramicization process, a glassy surface layer of about 50nm to 1000nm thick is formed, which is almost free of crystals and rich in these elements, wherein Li2O is exhausted. This glassy surface layer has a favorable effect on the acid resistance of the glass ceramic surface. In order to obtain a glassy layer of at least 50nm sufficient thickness, the minimum content of these two types of components (i.e. alkali metal and alkaline earth metal) is needed. Content above the upper limit can cause the thickness of the glass layer to be excessive, which is unfavorable for the intensity of glass ceramics.

[0089] ZnO

[0090] The ZnO component helps to lower the melting temperature and processing temperature of the glass, and reduces scattering under the condition of shortening the ceramicization time. ZnO is incorporated into the mixed crystal phase, and a part of it is also retained in the residual glass phase. Compared with the Li2O component, this component causes the thermal expansion of glass ceramics to decrease. Because the glass melt tends to vaporize, and glass ceramics require zero expansion, the ZnO content is limited to a value of up to 3wt.%. The ZnO content is preferably up to 2.5wt.%, particularly preferably up to 2.0wt.%. ZnO is preferably equal to 0wt.% or > 0wt.%. The minimum content is preferably 0.5wt.%, particularly preferably higher than 1wt.%. The ZnO content should preferably be 0.5wt.% to 3wt.%.

[0091] P2O5

[0092] In order to improve the meltability and devitrification resistance during the molding process, up to 4 wt.% of P2O may be included. 5。 Higher contents are detrimental to chemical resistance. Preferably, P2O5=0wt.% or >0wt.%. The lower limit is preferably 0.01wt.%, particularly preferably 0.02wt.%. The upper limit of P2O5 is preferably 2wt.%. The preferred range is 0.01wt.% to 4wt.%.

[0093] B2O3

[0094] Addition of up to 1 wt.% B2O3 also improves melting properties and resistance to devitrification, but is detrimental to the durability / temperature resistance of the glass-ceramic. The glass-ceramic is preferably technically free of B2O3, ie, its content is less than 1000 ppm.

[0095] Fe2O3

[0096] Due to the high cost of iron-poor batch raw materials, it is not economically viable to limit the Fe2O3 content in the crystallizable glass to a value below 0.008 wt.% (i.e. below 80 ppm). On the other hand, as the Fe2O3 content increases, the concentration of the Fe / Ti color-forming complex in the glass-ceramic also increases. The color (chromaticity) c* increases, and the brightness Y decreases through absorption. Therefore, the crystallizable glass and the glass-ceramic obtained therefrom should contain at most 0.025 wt.%, preferably at most 0.02 wt.% of Fe2O3.

[0097] Coloring compounds

[0098] Due to the reduced light transmittance and darkened color, the glass preferably does not contain other coloring compounds, such as Ce, Cr, Ni, Cu, V, Mo, W and / or S, which can cause yellow, orange or red color, except for unavoidable impurities. The content is preferably less than 20 ppm. The maximum content that can still be tolerated is 0.1 wt.%.

[0099] Clarifying agent

[0100] Fining may be aided by the addition of chemical fining agents such as arsenic oxide, antimony oxide or cerium oxide and fining additives such as manganese oxide, sulfides and halides in a total content preferably up to 2.0 wt.%.

[0101] In a preferred embodiment, the crystallizable glass or the LAS glass ceramics made therefrom has an environmentally friendly composition. It should be understood that the composition is technically free of arsenic oxide and antimony oxide as conventional fining agents, ie, the content thereof is preferably less than 1000 ppm.

[0102] Both components may be present as impurities in amounts below 0.2 wt.%, preferably below 0.1 wt.%, particularly preferably below 500 ppm. In special cases, arsenic-containing foreign matter fragments are added to the transparent glass ceramic during the melting process for recycling reasons, but otherwise this addition is preferably omitted.

[0103] Preferably, the addition of halides as fining aids is also omitted. They vaporize during melting and enter the bath atmosphere. In this way, corrosive compounds such as HF, HCl and HBr are formed, which can adversely attack refractory bricks in the bath and exhaust system. Therefore, apart from unavoidable impurity contents, the glass and glass ceramics are preferably free of F, Cl, Br, and their respective contents are generally below 500 ppm.

[0104] Preferably, cerium oxide and antimony oxide are not used because they deteriorate the color of the transparent glass-ceramic.

[0105] CoO

[0106] By adding CoO in an amount up to 30 ppm, decolorization can be assisted. The CoO content is preferably 0.1 ppm to 20 ppm CoO. Above 30 ppm, CoO produces a reddish tint in the transparent glass ceramic.

[0107] Nd2O3

[0108] The Nd2O3 content may be 0wt.% or >0wt.%.

[0109] In the case of the transparent glass ceramics made of the lithium aluminosilicate glass according to the present invention, in a preferred embodiment, the interference color originating from the Fe / Ti color-forming complex and / or the Sn / Ti color-forming complex can be reduced by adding Nd2O3 in an amount of 0.005wt.% to 0.5wt.%. When it is less than 0.005wt.%, the decolorization effect is slight, and the lower limit of Nd2O3 is preferably 0.01wt.%, especially 0.03wt.%. When it exceeds 0.5wt.%, the brightness is undesirably deteriorated due to the absorption of the Nd band in the visible light range. Therefore, it is preferred to add up to 0.2wt.%. The preferred range of Nd2O3 is 0.005wt.% to 0.5wt.%.

[0110] If a component fraction is specified as 0 wt.%, this means that the raw material formulation does not contain the component in question. However, these components may be present as unavoidable impurities.

[0111] In a preferred embodiment, the crystallizable lithium aluminosilicate glass according to the present invention or the product made therefrom or the glass ceramic according to the present invention made therefrom preferably has the following composition (in terms of oxide wt.%):

[0112]

[0113]

[0114] The conditions are (both are calculated in wt.%): 0.005<MgO×SnO2<0.06 (Condition B1a).

[0115] According to another embodiment, the crystallizable lithium aluminosilicate glass or an article made therefrom or a glass ceramic made therefrom preferably has the following composition (in terms of oxide wt.%):

[0116]

[0117]

[0118] The conditions are (both are calculated in wt.%): 0.005<MgO×SnO2<0.06 (Condition B1a).

[0119] In order to further achieve the goal of low chromaticity as well as high light transmittance and economical production, the crystallizable lithium aluminosilicate glass or articles made therefrom or glass ceramics made therefrom have a particularly preferred composition (in terms of oxide wt.%):

[0120]

[0121] The conditions are (both are calculated in wt.%): 0.005<MgO×SnO2<0.06 (Condition B1a).

[0122] The above composition should be understood as the listed components accounting for at least 98 wt.%, generally 99 wt.% of the total composition. Compounds of various elements such as F, Cl, alkali metals Rb, Cs or elements Mn, Hf are common impurities in batch raw materials used on a large scale. Other compounds such as elements W, Nb, Ta, Y, Mo, rare earth elements, Bi, V, Cr, Ni may be present in small amounts, usually in the ppm range.

[0123] The water content of the crystallizable glass used to make glass ceramics is preferably 0.015 mol / l to 0.06 mol / l, depending on the choice of batch raw materials and the melting process conditions. This is equivalent to β -OH value is 0.16mm -1 Up to 0.64mm -1 During the conversion to glass ceramics, the infrared band changes, which is used to determine the water content. β -OH value changes, while water content remains unchanged. β For a method of determining the -OH value, see, for example, EP 1074520A1.

[0124] Preferably, the crystallizable glass has a 10 2 dPas temperature and / or processing temperature V up to 1330°C A and / or specific processing temperature V A At least 15℃ lower devitrification limit OEG 。

[0125] The bubble quality of the crystallizable lithium aluminosilicate glass and the glass ceramics produced therefrom corresponds to the bubble number requirement, which is preferably less than 5 bubbles / kg, preferably less than 2 bubbles / kg. This applies to bubbles that are greater than 0.1 mm in one dimension. This is preferably achieved by a low content of the fining agent SnO2 according to the invention and / or preferably by additional technical measures (e.g. a melt pool structure with walls and / or nozzles) to ensure energy utilization and melt pool melting capacity.

[0126] Since general measures according to the invention for sufficient refining at low SnO2 contents, such as adapting the bath melting volume or due to structural measures of the bath, may lead to additional costs, the crystallizable glass is preferably high-temperature refined at temperatures above 1750°C.

[0127] Glass Ceramics

[0128] Crystallizable lithium aluminosilicate glass is converted into glass-ceramics via a multi-stage temperature process.

[0129] The glass ceramic has the same composition as lithium aluminosilicate glass.

[0130] The glass ceramic is preferably transparent.

[0131] According to the first embodiment, the glass ceramic contains high quartz mixed crystals as a main crystal phase.

[0132] In order to minimize the scattering of glass ceramics containing high quartz mixed crystals as the main crystalline phase, it is advantageous to minimize the crystallite size. However, to date, this has generally required longer nucleation times and ceramicization times, which is economically very disadvantageous. When glass ceramics are obtained using the composition according to the invention, the nucleation and crystallization processes proceed faster, so that the ceramicization time can be shortened.

[0133] Due to the shortened ceramicization time, the high quartz mixed crystals of the glass ceramic preferably have an average crystallite size of at least 25 nm after ceramicization. The average crystallite size is particularly preferably greater than 35 nm. Due to increased scattering, the preferred upper limit is an average crystallite size of less than 50 nm.

[0134] The proportion of the high-quartz mixed crystal phase of the glass ceramic is preferably at least 60 wt.%, preferably at most 80 wt.%. These ranges have the advantage that the desired mechanical and thermal properties of the glass ceramic are achieved.

[0135] For a 4 mm thick transparent glass ceramic, the brightness Y is preferably greater than 83%, preferably greater than 84%, particularly preferably greater than 85%.

[0136] The chromaticity c* is preferably at most 4, preferably less than 3.5, particularly preferably less than 3.

[0137] The lightness and chromaticity values ​​are valid for measurements made with standard light D65 at 2° on polished samples 4 mm thick according to DIN 5033.

[0138] According to ASTM D1003-13, scattering (haze) is measured on polished samples of 4 mm thick LAS glass ceramics. The haze value is preferably below 2.5%, more preferably below 2%, and particularly preferably below 1.8%. Haze values ​​above 2.5% are generally visually disturbing. Values ​​below 2% are preferred, otherwise scattering in dark (i.e., for example, black) bottom coatings will be noticeable.

[0139] The transparent glass ceramic according to the invention has no visually disruptive light scattering. Thus, the appearance of objects and the bottom coating is not distorted. Illuminated displays (such as displays or screens) beneath the glass ceramic plate are clearly visible, sharply defined and without scattering.

[0140] The features of the glass ceramic according to the invention are preferably based on a defined composition (corresponding to the glass green body used to produce the glass ceramic) in combination with a controlled rapid ceramization (total duration of less than 300 minutes), as described by way of example with respect to the method according to the invention.

[0141] In the temperature range from room temperature to 700°C, the thermal expansion of the glass ceramic is preferably adjusted to about 0±0.5·10 -6 / The value of K.

[0142] In another embodiment, the glass ceramic comprises keatite mixed crystal as the main crystalline phase. For economic reasons, advantageously, the same composition of crystallizable lithium aluminum silicate glass can be used to manufacture transparent glass ceramics containing high quartz mixed crystal as the main crystalline phase and can also manufacture glass ceramics containing keatite mixed crystal as the main crystalline phase. By designing the ceramicization program, especially by selecting the maximum temperature and the holding time, the outward appearance of the latter can be set to from transparent to semi-transparent to opaque.

[0143] The terms "opaque", "translucent" and "transparent" can be understood from the application perspective of the LED indication capability of glass ceramic products. Due to the unsatisfactory indication capability, the areas of low brightness Y with a transmittance below 2% of the glass ceramic plate are called opaque areas. Areas with higher brightness but visible scattering haze values ​​above 2.5% are considered translucent.

[0144] The average crystallite size is preferably greater than 60 nm. The proportion of the crystalline phase is greater than 60 wt.%, preferably greater than 80 wt.%. The combination of different properties of the two glass-ceramic embodiments allows economically advantageous use in a large number of applications.

[0145] The preferred geometric shape of the glass ceramic according to the invention or the product made therefrom is plate-shaped. The plate thickness is preferably 2 mm to 20 mm, which opens up certain important applications. Thinner thicknesses will weaken the strength, and thicker thicknesses will be less economical due to higher material requirements. Except for applications as high-strength safety glass, the thickness is preferably selected to be less than 6 mm.

[0146] The preferred product according to the present invention is a calendered glass ceramic plate. The maximum area size of the product is limited by the scope of hot forming (calendering or float) and the size of the ceramic melting furnace in the manufacture. For some applications, such as fireproof glass or kitchen worktops with integrated cooking areas, a size of up to 3m of edge length is preferred, because this size can meet the layer height of windows and stovetops in large kitchens.

[0147] Glass ceramic plates and preferably articles made therefrom can be not only flat, but also three-dimensionally deformed. For example, chamfered, beveled or curved plates can be used. These plates can be rectangular or other shapes, and except the flat area, also comprise three-dimensionally deformed areas, such as pots, rolling strips, convex surfaces or concave surfaces. In hot forming, for example, by structured forming rollers or by hot forming downstream of the initial glass, for example, by burners, infrared radiators or by gravity settling, the geometric deformation of the plate is carried out. During ceramicization, the flat substrate is processed using the ceramic shape of support to avoid uncontrolled changes in geometry. If the application requires, subsequent polishing can be optionally carried out to one or both sides.

[0148] Glass manufacturing method

[0149] The method for producing a crystallizable lithium aluminosilicate glass according to the present invention is characterized by the following steps:

[0150] a) Providing bulk ingredients made from technical raw materials;

[0151] b) melting the batch ingredients and performing high temperature fining at a temperature above 1750° C.;

[0152] c) Cooling the glass melt and heating it to near the processing temperature V A forming at a temperature of

[0153] d) Cooling to room temperature in an annealing furnace, wherein undesirable stresses in the glass are eliminated.

[0154] Room temperature refers to 20°C.

[0155] The batch is formed so that after melting, a glass having the composition and properties according to the present invention is produced. Preferably, 20 wt.% to 80 wt.% of cullet is added to the batch, whereby melting is promoted and a higher melting amount of the molten bath can be obtained. A high temperature fining unit is used, and the temperature of the glass melt in the molten bath is higher than 1750°C, preferably higher than 1850°C. During forming, a glass ribbon having a plate-like geometry is preferably manufactured by rolling and cooled to room temperature in an annealing furnace to remove stress. After ensuring the quality in terms of volume defects and surface defects, a plate of the desired size is produced from this glass ribbon.

[0156] By reducing the viscosity of the glass melt at high temperatures, a low melting temperature can be ensured, which is beneficial for economical production. For this purpose, the viscosity of the glass melt is 10 2 The temperature at which 10 dPas is reached is a characteristic variable. 2 The temperature at dPas is preferably below 1760° C., preferably below 1755° C., and particularly preferably below 1750° C. The low viscosity of the glass melt at high temperatures allows the temperature in the melting pool to be adjusted lower, thereby extending the service life of the melting pool. This reduces energy consumption related to the amount of glass ceramic produced. Low glass viscosity is also beneficial to the rise of bubbles and thus to clarification, so low glass viscosity is also beneficial to bubble quality.

[0157] It is economically advantageous to reduce the temperature during forming. The service life of the forming mold is extended and less heat is lost. Forming is usually carried out by calendaring or float method, and the viscosity of the molten glass is 10 4 dPas. This temperature is also called processing temperature V A , for the glasses according to the invention, preferably at most 1330° C., preferably at most 1325° C.

[0158] If formed from the melt, the crystallizable glass has sufficient resistance to devitrification. If formed in contact with a forming material (e.g., a precious metal in a drawing nozzle during calendering), no visually obvious crystals critical to the strength of the glass-ceramic will form in the glass. The limit temperature below this critical devitrification, i.e., the upper devitrification limit (OEG), preferably below the processing temperature V A , especially preferably the processing temperature V A At least 15°C lower. At this minimum temperature difference, a sufficient process window is defined for the forming process. Particularly advantageously, the process window V A –OEG is at least 20°C. Temperature difference V A –OEG is a measure of resistance to devitrification.

[0159] Suitable forming methods for plate-shaped geometries are, in particular, calendering and float processes. A forming method using a glass melt is preferred, which is a two-fold calendering process, which has the advantage of a faster cooling rate when the components tend to devitrify.

[0160] Ceramic method

[0161] The next step of the method is to ceramize the flat or three-dimensionally shaped high temperature stable substrate (kiln furniture). Preferably, the ceramizing is carried out in a roller kiln.

[0162] The manufacturing method of the glass ceramic according to the present invention is characterized in that ceramicization is carried out in the following order using the following method steps:

[0163] a) raising the temperature of the crystallizable glass to a temperature T in the range of 660° C. to 730° C. within a period of 3 minutes to 60 minutes a ;

[0164] b) raising the temperature of the crystallizable glass to the nucleation temperature T within a period of 10 to 100 minutes a In the temperature range of up to 800°C;

[0165] c) raising the temperature of the crystal nucleus-containing glass to a temperature range of 850° C. to 950° C. for a high crystal growth rate within a period of 5 to 80 minutes;

[0166] d) maintaining the highest temperature in the temperature range of 850° C. to 950° C. for 0 to 60 minutes, wherein a high quartz mixed crystal type crystal grows on the crystal nucleus;

[0167] e) rapidly cooling the obtained glass-ceramic to room temperature in less than 150 minutes,

[0168] The ceramization of the glass has a total duration of less than 300 minutes.

[0169] The holding time in process step d) is preferably from 1 minute to 60 minutes.

[0170] The required high heating rates can be achieved on a large scale in a roller kiln. The temperature range of 660°C to 730°C corresponds approximately to the glass transition temperature. Temperatures above 730°C to 800°C are the range of high nucleation rates, with the temperature of maximum nucleation rate being 750°C to 760°C.

[0171] Experiencing T between 10 minutes and 100 minutes a The temperature of the glass containing the nuclei is then increased to a temperature of 850° C. to 950° C. over a period of 5 to 80 minutes, wherein a high rate of crystal growth of a high quartz mixed crystal phase is observed. The maximum temperature in the temperature range of 850° C. to 950° C. is maintained for 0 to 60 minutes. In this process, the structure of the glass ceramic is homogenized and its optical, physical and chemical properties are adjusted.

[0172] Thereafter, the obtained glass ceramic is rapidly cooled to room temperature within a period of more than 10 minutes but less than 150 minutes.

[0173] Generally speaking, the ceramization time is less than 300 minutes, preferably less than 200 minutes, and particularly preferably less than 150 minutes.

[0174] In addition, transparent LAS glass ceramics made from crystallizable glass have certain properties. The brightness Y should be high, while the chromaticity c* should be low, so that the perspective and display appearance on the object or the bottom coating is not darkened or the color is distorted. The transparent glass ceramic should not have any light scattering that interferes with vision, so that the perspective and display are clear and unobstructed. This should also be ensured by trying to shorten the ceramicization time.

[0175] The content of the components responsible for forming the crystalline phase and the residual glass is optimized, and high brightness values, low chromaticity and little scattering can be obtained even when the ceramicization time is shortened. Shortening the ceramicization time is understood to be less than 300 minutes, preferably less than 150 minutes, and particularly preferably less than 100 minutes. The glass ceramic is made from LAS crystallizable glass.

[0176] Within these preferred ranges, in combination with further specified composition ranges, the desired effects of minimizing chromaticity, increasing brightness, and favorable manufacturing characteristics are produced, such as particularly advantageously by combining rapid ceramization with low melting temperature and processing temperature V A Minimize light scatter.

[0177] Glass ceramics use

[0178] Transparent lithium aluminum silicon glass ceramics containing high quartz mixed crystals as the main crystal phase are preferably used as fireproof glass, fireplace windows, oven windows (especially for pyrolysis furnaces), stove tops (which may have a bottom coating), covers in the lighting field, safety glass panels (preferably for laminated composites), carrier plates or kiln linings (preferably for heat treatment).

[0179] A good view of the combustion chamber and the flames is desirable for fireplace windows. If the cooktop has a colored base coating, the color of the base coating should not be distorted by the color of the glass ceramic. For the above-mentioned uses, high brightness values ​​Y and low chromaticity c* with insignificant light scattering are preferred according to the invention.

[0180] By applying an opaque coating on the top and / or bottom, colored cooktops can be produced from transparent glass ceramics with the desired visual coverage, so that the technological built-in components below the cooktop are not visible. As usual, the cooktop is heated using a gas burner, radiant heating or induction heating.

[0181] Recesses in the coating allow for the application of sensor areas, color and white indicating devices and displays.

[0182] It is possible to combine coatings on the top and bottom of the transparent glass ceramic plate, which may also include partially transparent layers. It is also possible to apply markings, for example for cooking areas. Different types of coatings are known, which may be combined, for example, with organic or inorganic decorative pigments, luster pigments, silicone-based and sol-gel-based pigments, sputtered layers, metal layers, oxynitride layers, oxycarbide layers, etc. These layers may also be superimposed on one another.

[0183] In chimney windows or oven windows, coatings may also be required, for example to cover the edges of the panes opaquely. The arrangement of coatings on the top and bottom sides of the glass ceramic panels meets aesthetic requirements as well as specific requirements for chemical and physical properties.

[0184] The indicating device consists of light-emitting electronic components, such as light-emitting diodes, OLEDs, LCDs or fluorescent indicators. There can be various forms of indicators, dot matrix and area matrix displays, including seven-segment displays. The emission spectrum of the radiation indicator can have one or more maxima and a wide spectrum, so that the indicator appears in color (such as blue, purple, red, green, yellow and orange) or white. Due to the low chromaticity c* of glass ceramics, black and white and color displays or screens can also be manufactured without interfering color distortion. Optionally, the color of the display is changed by attaching a color filter or pigment layer to the bottom surface. The indicator color may be affected, and if necessary, the indicator color that changes due to glass ceramics can also be corrected. For example, capacitive or inductive control elements, sensor elements and manipulation / operating elements can be attached to the glass ceramic plate.

[0185] Alternatively, these uses can also be achieved by transparent, translucent or opaque lithium aluminum silicon glass ceramics, in which hot quartz mixed crystals are the main crystal phase. It is preferably used as a stove top, a support plate (backing plate) for heat treatment, a cover plate in a microwave oven or a radiator, and a lining of a combustion chamber, and is in a translucent or opaque form. In this case, the brightness Y is preferably less than 30%.

[0186] The further preferred use of two kinds of glass ceramics is to be used as carrier plate or kiln lining, and they contain high quartz mixed crystal or keatite mixed crystal as main crystalline phase.In ceramic industry, solar energy industry or pharmaceutical industry or medical technology, they are particularly suitable for the manufacturing process under ultrapure condition, for example wherein carry out the kiln lining of chemical or physical coating process, or as chemical resistance laboratory equipment.They can also be used as glass ceramic objects of high temperature or extremely low temperature application, kiln window of incineration kiln, the heat shield of shielding high temperature environment, for reflector, floodlight, projector, slide projector, cover plate of photocopier (being applicable to the application with thermomechanical stress, for example night vision equipment) or for cover plate of heating element, especially stove surface, grilling surface or baking surface, white goods, heater cover, wafer substrate, UV protection object, cladding board or for example material and / or IT cover glass (for example mobile phone, laptop computer, scanner glass) or bulletproof component of electronic equipment housing component. BRIEF DESCRIPTION OF THE DRAWINGS

[0187] The present invention is described according to the following examples.

[0188] Figure 1 The transmission curve graph of the glass ceramic of Example 13 (Glass No. 11) in Table 1 is shown;

[0189] Figure 2 An explanatory diagram showing the shift of the absorption band. DETAILED DESCRIPTION

[0190] The LAS crystallizable glasses Nos. 1 to 11 according to the present invention and the comparative glasses Nos. 12 to 18 were obtained by melting batch raw materials customary in the glass industry at a temperature of 1620° C. for 4 hours.

[0191] The following raw materials can be optionally used: lithium carbonate, aluminum oxide, aluminum hydroxide, aluminum metaphosphate, quartz sand, sodium nitrate and potassium nitrate, sodium carbonate and potassium carbonate, magnesium oxide, calcium salt, dolomite, strontium carbonate, barium carbonate, zinc oxide, tin oxide, titanium oxide, zirconium silicate, zirconium oxide, and optionally neodymium oxide.

[0192] The main raw materials and technical raw materials for introducing Li2O are preferably those with a Fe2O3 content of less than 150 ppm, such as quartz, alumina, aluminum hydroxide and lithium carbonate. Through this selection, the requirements for economic raw materials can be coordinated with the requirements for low impurity content of coloring compounds containing Fe, Ni, Cr, V, Cu, Mo, and S.

[0193] After melting the batch in a crucible made of sintered quartz glass, the laboratory melt was poured into a Pt / Rh crucible with an inner crucible made of quartz glass and homogenized by stirring for 60 minutes at a temperature of 1600° C. After homogenization, the glass was refined at 1640° C. for 3 hours. Since it was a laboratory melt, high-temperature refining was not performed.

[0194] Then cast into approximately 120×140×30mm 3 The castings are then cooled from 660°C to room temperature in an annealing furnace to relieve stress. The castings are cut into the required sizes for testing and ceramicization. Glass No. 11 is melted on an industrial scale in a production bath.

[0195] Table 1 shows the composition and characteristics of crystallizable glass. In addition to the component content, the relevant component relationship is also shown. Here, glasses No. 1 to 11 are glasses according to the present invention, i.e., embodiments, while glasses No. 12 to 18 are comparative glasses outside the present invention, i.e., comparative examples. The composition of comparative glasses No. 12 to 18 is not within the scope of the present invention and shows the disadvantages described in terms of manufacturing characteristics (melting temperature, processing temperature, anti-devitrification, roller coating) and / or chromaticity, brightness and scattering after conversion into glass ceramics. Due to typical impurities in the large-scale batch raw materials used, the addition amount of this component is not completely equal to 100wt.%. Even if typical impurities are accidentally introduced into the composition, its F, Cl, B, Mn, Rb, Cs, Hf are usually less than 0.2wt.%. They are usually brought in by the raw materials of the components used, for example, Rb and Cs are brought in by Na raw materials or K raw materials, or Hf is brought in by Zr raw materials.

[0196] Table 1 indicates the water content of the crystallizable glasses measured by infrared spectroscopy.

[0197] Table 1 also lists the properties of the glass state, transition temperature Tg [℃], processing temperature V A [℃], 10 2 dPas temperature [℃], devitrification upper limit OEG [℃] and devitrification resistance V A – OEG. To measure OEG, the glass was melted in a Pt / Rh10 crucible. Subsequently, the crucible was kept at different temperatures within the processing temperature range for 5 hours. The highest temperature at which the first crystals appeared at the contact surface between the glass melt and the crucible wall determined the OEG temperature.

[0198] Table 2 relates to glass ceramics containing high quartz mixed crystals as a main crystal phase, which are obtained from the glasses in Table 1. Here, Examples 1 to 13 are Examples, and Examples 14 to 20 are Comparative Examples.

[0199] For the corresponding designated ceramizing procedures, namely Procedure 1 and Procedure 2, Table 2 shows the properties of the glass ceramics, namely the spectral transmittance at 400 nm [%], the infrared transmittance at 1600 nm [%], the temperature at 20°C to 700°C [10 -6 Table 2 also shows the transmittance Y in the CIE color system and the color coordinates L*, a*, b* and the variable c* (as a measure of chromaticity) in the CIELAB color system, as well as the haze value (as a measure of scattering).

[0200] Table 3 shows Examples 21 and 22 of glass ceramics having keatite mixed crystals as the main crystal phase, which were obtained from glass No. 10 in Table 1. In addition to the transmittance values, color values ​​for measuring reflectivity are also shown. The appearance of these examples is also qualitatively described.

[0201] Ceramicization procedures 1–3

[0202] In ceramization procedure 1, heating to 720° C. in a laboratory furnace can be achieved within 24 minutes at a high heating rate. In the temperature range from 720° C. to 800° C., the heating rate is reduced for sufficient nucleation so that no visually disturbing scattering occurs.

[0203] Since high quartz mixed crystals will crystallize in this range, the heating rate is further reduced when it exceeds 800°C until the maximum temperature of 890°C. The shrinkage process associated with it cannot be too fast, otherwise the product may be uneven. In this temperature range, the formation of interfering Fe / Ti color-forming complexes and Sn / Ti color-forming complexes will also be enhanced. The total time from 800°C to the maximum temperature of 890°C is 53 minutes, and the subsequent holding time is 10 minutes. At the highest temperature, the composition of the crystals and residual glass is adjusted to homogenize the microstructure. Adjust the chemical and physical properties of the glass-ceramic. Control the cooling to 600°C, and then quench the sample to room temperature by opening the kiln door.

[0204] Ceramicization procedure 1 (ceramicization time 136 minutes):

[0205] Rapid heating from room temperature to T in 24 minutes a =720℃;

[0206] In 20 minutes, the temperature was reduced from T a =720℃ to 800℃ (heating rate up to 4℃ / min);

[0207] The temperature was increased from 800°C to 890°C in 53 minutes (heating rate of 1.7°C / min);

[0208] Maintain the maximum temperature of 890°C for 10 minutes;

[0209] Cooling from 890°C to 600°C in 29 minutes (at 10°C / min)) followed by rapid cooling to room temperature.

[0210] In ceramicizing procedure 2, the ceramicizing time is generally shortened and the nucleation time is extended. In ceramicizing procedure 2, the ceramicizing furnace is heated to a temperature of 720°C within 24 minutes. In the temperature range of 720°C to 800°C, the heating rate is further reduced for sufficient nucleation so that no visually disturbing scattering occurs. The total time from 720°C to 800°C is 33 minutes. Above 800°C, crystallization of the desired high quartz mixed crystal phase occurs. The total time from 800°C to reaching the maximum temperature of 885°C is 28 minutes. At the maximum temperature of 885°C, it is maintained for 10 minutes to adjust to the composition of the crystals and residual glass and to homogenize the microstructure. Controlled cooling to 800°C at a cooling rate of 8.5°C / min within 10 minutes, and then the sample is quenched to room temperature by opening the furnace door. In summary:

[0211] Ceramicization procedure 2 (ceramicization time 105 minutes):

[0212] Rapid heating from room temperature to T in 24 minutes a =720℃(heating rate up to 30℃ / min);

[0213] In 33 minutes, the temperature was reduced from T a =720℃ to 800℃ (heating rate up to 2.4℃ / min);

[0214] The temperature was increased from 800°C to 885°C in 28 minutes, during which it was heated to 820°C at a rate of 1°C / min and further heated to 885°C at a rate of 8°C / min;

[0215] Maintain the highest temperature of 885℃ for 10 minutes.

[0216] Cool to 800°C in 10 minutes and then quickly cool to room temperature.

[0217] By means of an additional ceramization procedure 3, the crystallizable glass No. 10 (Table 1) is converted into a glass ceramic containing a keatite mixed crystal as the main crystalline phase. In this procedure, the temperature is 885°C (step d) as in procedure 2, and then, unlike procedure 1, the temperature is not kept at 885°C and is heated to a maximum temperature T at a heating rate of 10°C / min without a holding time. max , keep time t max (See Table 3 for details) The highest temperature was cooled to 800°C at a rate of 10°C / min, and then rapidly cooled to room temperature.

[0218] The transmittance measurements were carried out on 4 mm thick polished panels using a Perkin-Elmer Lambda 900 instrument with standard light D65 at 2°. For the selected standard light source D65 and observer angle 2°, the brightness Y was calculated according to standard DIN 5033 from the spectral measurements in the range of 380 nm to 780 nm representing the visible spectrum.

[0219] The color coordinates L*, a*, b* and the variable c* in the CIELAB color system are also calculated from these measured values. Reflectance measurements according to standard DIN 5033 are also carried out using these parameters.

[0220] The scattering in glass ceramics is determined by measuring the haze. The haze is measured in accordance with ASTM D1003-13 using the commercial measuring instrument "haze-guard plus" from BYK-Gardner on 4 mm thick panels using standard light C and characterized by the haze value.

[0221] Melting of glass No. 11 on an industrial scale. The composition is optimized according to the requirements of economic production and transparency of lithium aluminosilicate glass ceramics. It is characterized by low 10 2 dPas temperature, low processing temperature V A , and good resistance to devitrification. The glass melt was clarified at a high temperature of about 1850°C for 15 minutes. The bubble quality of the glass is excellent, i.e. <2 bubbles / kg of glass. During forming, a 4mm thick glass ribbon with smooth double sides was rolled and cooled in an annealing furnace to avoid stress. Compared with glasses with higher SnO2 content, the formation of Sn-containing roller coatings is reduced. A 500mm×500mm×4mm plate was cut from the glass ribbon and ceramicized in a large roller kiln. The ceramicization procedure is equivalent to procedure 2, and the crystallizable glass plate is located on a flat pad. The flatness of the obtained transparent glass ceramic plate is excellent, less than 0.3% of the side length. The properties of the glass ceramics are shown in Table 2 as Example 13. Figure 1 The transmittance curve of the glass ceramic according to the invention is shown in . The transparency corresponds to the advantageous values ​​according to the invention, with a brightness Y of 84.7% and a chromaticity c* of 3.1, without visually disturbing scattering.

[0222] As for the other comparative glass 18 (see Table 1), the composition of glass No. 1 is basically adopted, but the MgO content is increased to 0.77 wt.%. Comparative glass 19 is converted into glass ceramic using ceramic process 1 (see comparative example 20 in Table 2). Figure 2 The comparison is made in Table 1 of Example 1 according to the present invention. Example 1 is glass No. 1 which is also converted according to the same ceramization procedure 1. Figure 2The effect of the above-mentioned shift of the absorption band due to different MgO contents is shown. In the blue range of visible light, the Sn / Ti absorption band is affected by its intensity and its position in the visible spectrum. Due to the conditions of the MgO content and the composition product MgO×SnO2 according to the invention, a higher spectral transmittance is achieved in the short-wave spectral range, which has a very favorable effect on the chromaticity c*. Compared with MgO×SnO2=0.22 and chromaticity c*=2.6 in Example 1, the values ​​in Comparative Example 20 are MgO×SnO2=0.06 and c*=3.2.

[0223] The following typical impurities were analyzed: 0.04wt.% HfO2, 8ppm As2O3, 1ppm Cr2O3, 1ppm CuO, 3ppm MnO2, 4ppm MoO 3、 1ppm NiO, 3ppm V2O5.

[0224] Table 1: Composition and properties of crystallizable glasses

[0225] Glass No. 1 2 3 4 5 6 Element wt.% <![CDATA[Li2O]]> 3.68 3.23 3.27 3.25 3.32 3.29 <![CDATA[Na2O]]> 0.56 0.45 0.37 0.45 0.61 0.62 <![CDATA[K2O]]> 0.09 0.58 0.36 0.58 0.30 0.30 MgO 0.27 0.33 0.28 0.15 0.36 0.36 CaO 0.39 0.76 0.59 0.77 0.75 0.75 SrO 0.05 0.02 0.02 0.10 0.10 BaO 0.88 1.74 1.78 1.73 1.33 1.32 ZnO 1.75 1.88 1.99 1.86 1.85 1.81 <![CDATA[Al2O3]]> 21.4 21.4 21.3 21.5 21.5 21.3 <![CDATA[SiO2]]> 66.6 65.3 65.5 65.5 65.6 65.1 <![CDATA[TiO2]]> 2.29 2.29 2.54 2.29 2.34 2.30 <![CDATA[ZrO2]]> 1.83 1.83 1.83 1.83 1.83 1.81 <![CDATA[P2O5]]> 0.03 0.03 0.03 0.03 0.03 <![CDATA[SnO2]]> 0.08 0.09 0.08 0.08 0.09 0.02 <![CDATA[Fe2O3]]> 0.014 0.014 0.014 0.013 0.014 0.014 <![CDATA[Nd2O3]]> 0.051 0.049 <![CDATA[As2O3]]> 0.89 <![CDATA[H2O content (β-OH)]]> <![CDATA[mm -1 ]]> 0.37 0.38 0.36 0.39 0.39 0.31 <![CDATA[MgO×SnO2]]> 0.022 0.028 0.023 0.012 0.031 0.007 <![CDATA[TiO2 / SnO2]]> 28.6 26.9 31.0 28.6 27.5 115.0 <![CDATA[Na2O+K2O]]> 0.65 1.03 0.73 1.03 0.91 0.92 SrO+BaO 0.93 1.74 1.80 1.75 1.43 1.42 <![CDATA[TiO2+ZrO2+SnO2]]> 4.20 4.21 4.45 4.20 4.26 4.13 <![CDATA[Na2O / K2O]]> 5.96 0.78 1.03 0.78 2.03 2.07 Glass-like properties <![CDATA[Transition temperature T g > ℃ 685 683 690 692 684 682 <![CDATA[10 2 dPas temperature]]> ℃ 1755 1745 1737 1748 1736 1733 <![CDATA[Processing temperature V A > ℃ 1320 1316 1315 1325 1316 1313 OEG Temperature ℃ 1265 1275 1280 1270 1255 1290 <![CDATA[Devitrification resistance V A –OEG]]> ℃ 55 41 35 55 61 23

[0226] Table 1 (continued): Composition and properties of crystallizable glasses

[0227] Glass No. 7 8 9 10 11 Element wt.% <![CDATA[Li2O]]> 3.46 3.70 4.02 3.71 3.69 <![CDATA[Na2O]]> 0.57 0.54 0.54 0.53 0.58 <![CDATA[K2O]]> 0.41 0.16 0.16 0.16 0.09 MgO 0.32 0.28 0.28 0.28 0.29 CaO 0.50 0.40 0.40 0.40 0.37 SrO 0.10 0.05 0.05 0.05 0.10 BaO 1.48 0.92 0.93 0.93 0.81 ZnO 1.86 1.78 0.82 1.76 1.72 <![CDATA[Al2O3]]> 21.2 21.6 21.7 21.6 21.5 <![CDATA[SiO2]]> 65.7 66.2 66.1 66.2 66.5 <![CDATA[TiO2]]> 2.40 2.35 2.42 2.36 2.20 <![CDATA[ZrO2]]> 1.83 1.83 1.83 1.83 1.83 <![CDATA[P2O5]]> 0.03 0.03 0.66 0.03 0.02 <![CDATA[SnO2]]> 0.08 0.045 0.043 0.069 0.12 <![CDATA[Fe2O3]]> 0.014 0.015 0.014 0.013 0.013 <![CDATA[Nd2O3]]> 0.049 0.052 0.053 <![CDATA[As2O3]]> 0.0008 <![CDATA[H2O content (β-OH)]]> <![CDATA[mm -1 ]]> 0.43 0.40 0.37 0.45 0.42 <![CDATA[MgO×SnO2]]> 0.027 0.013 0.012 0.019 0.035 <![CDATA[TiO2 / SnO2]]> 28.9 52.2 56.3 34.2 18.3 <![CDATA[Na2O+K2O]]> 0.98 0.70 0.70 0.69 0.67 SrO+BaO 1.58 0.97 0.98 0.98 0.91 <![CDATA[TiO2+ZrO2+SnO2]]> 4.31 4.23 4.29 4.26 4.15 <![CDATA[Na2O / K2O]]> 1.39 3.38 3.38 3.31 6.44 Glass-like properties <![CDATA[Transition temperature T g > ℃ 680 684 688 683 684 <![CDATA[10 2 dPas temperature]]> ℃ 1742 1742 1746 1747 1749 <![CDATA[Processing temperature V A > ℃ 1314 1316 1321 1318 1320 OEG Temperature ℃ 1280 1275 1260 1290 1280 Devitrification resistance VA-OEG ℃ 34 41 61 28 40

[0228] Table 1 (continued): Comparison of composition and properties of crystallizable glasses

[0229]

[0230] Table 2: Ceramics conditions and properties of glass ceramics with high quartz mixed crystals as the main crystal phase

[0231]

[0232] Table 2 (continued): Ceramics conditions and properties of glass ceramics with high quartz mixed crystals as the main crystal phase

[0233]

[0234] Table 2 (continued): Ceramics conditions and properties of comparative glass ceramics with high quartz mixed crystals as the main crystal phase

[0235]

[0236] Table 3: Ceramics conditions and properties of glass ceramics with keatnetite mixed crystals as the main crystal phase

[0237]

Claims

1. A crystallizable lithium aluminosilicate glass for making transparent glass ceramics, characterized in that: It contains the following components in terms of oxide wt.%: When both are measured by wt.%, the condition is: 0.005<MgO×SnO2<0.06, i.e. condition B1a, Wherein, the glass does not contain Ce, Cr, Ni, Cu, V, Mo, W and S except for unavoidable impurities.

2. The crystallizable lithium aluminosilicate glass according to claim 1, characterized in that The product of the components MgO and SnO2 applies: 0.01<MgO×SnO2<0.05, ie condition B1b.

3. The crystallizable lithium aluminosilicate glass according to any one of the preceding claims, characterized in that For components TiO2 and SnO2, the following applies: 18≤TiO2 / SnO2≤200, i.e. condition B2.

4. The crystallizable lithium aluminosilicate glass according to any one of the preceding claims, characterized in that The nucleating agent is applicable to: 3.8wt.%≤TiO2+ZrO2+SnO2≤4.8wt.%, that is, condition B3.

5. The crystallizable lithium aluminosilicate glass according to any one of claims 1 to 4, characterized in that It contains Na2O in a proportion of 0.1 wt.% to 1.5 wt.%.

6. The crystallizable lithium aluminosilicate glass according to any one of claims 1 to 5, characterized in that It contains K2O in a proportion of 0.1 wt.% to 1.5 wt.%, Preferably, the following applies: 0.2wt.%≤Na2O+K2O≤1.5wt.%, i.e. condition B4a; And / or applicable: 1≤Na2O / K2O≤10, i.e. condition B5.

7. The crystallizable lithium aluminosilicate glass according to any one of the preceding claims, characterized in that It contains CaO in a proportion of 0.05 to 2 wt.%.

8. The crystallizable lithium aluminosilicate glass according to any one of the preceding claims, characterized in that It contains BaO in a proportion of 0.2 to 2.5 wt. %.

9. The crystallizable lithium aluminosilicate glass according to any one of the preceding claims, characterized in that It contains SrO in a proportion of 0.01 wt.% to 2 wt.%, Preferably, the following applies: 0.5wt%≤SrO+BaO≤2.5wt%, ie, condition B6.

10. The crystallizable lithium aluminosilicate glass according to any one of the preceding claims, characterized in that It contains ZnO in a proportion of 0.5 to 3 wt. %.

11. The crystallizable lithium aluminosilicate glass according to any one of the preceding claims, characterized in that It contains P2O5 in a proportion of 0.01 wt.% to 4 wt.%.

12. The crystallizable lithium aluminosilicate glass according to any one of the preceding claims, characterized in that The glass is technically free of arsenic oxide and antimony oxide.

13. The crystallizable lithium aluminosilicate glass according to claim 1, characterized in that It contains the following components in terms of oxide wt.%: Among them, 0.005<MgO×SnO2<0.06, that is, condition B1a; Alternatively, the crystallizable lithium aluminosilicate glass comprises the following components in terms of oxide wt. %: Among them, 0.005<MgO×SnO2<0.06, that is, condition B1a.

14. The crystallizable lithium aluminosilicate glass according to any one of the preceding claims, characterized in that 10 2 dPas temperature is below 1760°C, and / or Processing temperature V A Up to 1330°C, and / or · The upper limit of devitrification OEG is higher than the processing temperature V A At least 15℃ lower.

15. The crystallizable lithium aluminosilicate glass according to any one of the preceding claims, characterized in that The number of bubbles is less than 5 bubbles / kg, preferably less than 2 bubbles / kg.

16. A glass ceramic produced from the lithium aluminosilicate glass according to any one of claims 1 to 15 by a multi-stage temperature process.

17. The glass ceramic according to claim 16, characterized in that The glass ceramic is transparent.

18. The glass ceramic according to claim 16 or 17, characterized in that: The glass ceramic contains high quartz mixed crystals as a main crystal phase.

19. The glass ceramic according to any one of claims 16 to 18, characterized in that For a thickness of 4 mm, the glass ceramic has a brightness Y of more than 83% and / or a chromaticity c* of at most 4 and / or a haze value of less than 2.5%.

20. The glass ceramic according to claim 16, characterized in that: The glass ceramic contains keatite mixed crystals as a main crystal phase.

21. The glass ceramic according to any one of claims 16 to 20, characterized in that The glass ceramic is in the form of a plate having a thickness of 2 mm to 20 mm.

22. A method for producing a crystallizable lithium aluminosilicate glass according to any one of claims 1 to 15, characterized by the following steps: a) Providing bulk ingredients made from technical raw materials; b) melting the batch ingredients and performing high temperature fining at a temperature above 1750° C.; c) Cooling the glass melt and heating it to near the processing temperature V A forming at a temperature of d) Cool to room temperature in an annealing furnace.

23. The method for producing glass ceramics according to any one of claims 16 to 21, characterized in that: Ceramicization is carried out by the following method steps: a) raising the temperature of the crystallizable glass to a temperature T in the range of 660° C. to 730° C. within a period of 3 minutes to 60 minutes a ; b) raising the temperature of the crystallizable glass to T for a period of about 10 minutes to 100 minutes a In the nucleation temperature range of 800°C; c) raising the temperature of the crystal nucleus-containing glass to a temperature range of 850° C. to 950° C. for a high crystal growth rate within a period of 5 to 80 minutes; d) maintaining the temperature at a maximum temperature in the range of 850° C. to 950° C. for 0 to 60 minutes, wherein a high quartz mixed crystal type crystal grows on the crystal nucleus; thereafter e) rapidly cooling the obtained glass-ceramic to room temperature in less than 150 minutes, In this case, the ceramization of the glass has a total duration of less than 300 minutes.

24. Use of the transparent glass ceramic plate according to claim 21 as fireproof glass, fireplace window, oven window, cooktop, cover plate in the lighting field, safety glass window, carrier plate or kiln lining.

Citation Information

Patent Citations

  • Li2O-Al2O3-SiO2 crystallized glass and crystallizable glass therefor

    EP1074520A1

  • Transparent, colorless low-titania beta-quartz glass-ceramic material

    WO2008065166A1

  • Transparent, colorless titania-free beta-quartz glass-ceramic material

    WO2008065167A1

  • Transparent low-colour lithium aluminium silicate glass ceramic and the use thereof

    WO2013124373A1

  • Transparent, essentially colorless and non-diffusing beta-quartz glass-ceramics; articles in said glass-ceramics; precursor glasses.

    WO2013171288A1